2016
DOI: 10.2169/internalmedicine.55.6084
|View full text |Cite
|
Sign up to set email alerts
|

Clindamycin-induced Kidney Diseases: A Retrospective Analysis of 50 Patients

Abstract: Objective There are many adverse reactions due to clindamycin, but kidney diseases (acute kidney injury, AKI) are uncommon. However, in recent years, the rate of clindamycin-induced kidney diseases has increased. We analyzed 50 patients with clindamycin-induced kidney diseases retrospectively, and investigated the characteristics of these kidney diseases in order to provide a reference for rational clinical drug use and to reduce drug-induced organ damage. Methods We investigated 50 patients diagnosed with cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…All reported patients thus far have been Asian, while our patient was African-American and the first reported case from North America. The most common symptoms on admission in the other 2 studies [10,11] were abdominal discomfort, nausea, and vomiting, similar to what our patient experienced. The median onset of AKI following clindamycin administration in the other 2 studies was between 1 and 4 days.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…All reported patients thus far have been Asian, while our patient was African-American and the first reported case from North America. The most common symptoms on admission in the other 2 studies [10,11] were abdominal discomfort, nausea, and vomiting, similar to what our patient experienced. The median onset of AKI following clindamycin administration in the other 2 studies was between 1 and 4 days.…”
Section: Discussionsupporting
confidence: 85%
“…We performed a literature search on PubMed database for articles using the following words alone or in combination: clindamycin side effect, AKI due to clindamycin, drug related AKI, acute interstitial nephritis (AIN) due to clindamycin, and acute tubular necrosis (ATN) due to clindamycin. While our search yielded no single case report published, we found 2 retrospective studies from China that described case series of biopsy proven AKI due to clindamycin [10,11]. The study by Wan et al [10] reported 50 patients and the study by Xie et al [11] reported a case series consisting of 24 patients with biopsy proven clindamycin-induced AKI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Postrenal acute kidney injury is often caused by urinary tract obstruction. [ 7 , 8 ] In many of cases, the decreased effective blood volume and presence of substances harmful to the kidney are the main causes of acute kidney injury in clinical practice.…”
Section: Discussionmentioning
confidence: 99%